Changing deserts: integrating people and their environment - Mol, Lisa, 1983-; Sternberg, Troy, 1959- (White Horse Press, 2012)
Deserts – vast, empty places where time appears to stand still. The very word conjures images of endless seas of sand, blistering heat and a virtual absence of life. However, deserts encompass a large variety of landscapes and life beyond our stereotypes. As well as magnificent Saharan dunes under blazing sun, the desert concept encompasses the intensely cold winters of the Gobi, the snow-covered expanse of Antarctica and the rock-strewn drylands of Pakistan. Deserts are environments in perpetual flux and home to peoples as diverse as their surroundings, peoples who grapple with a broad spectrum of cultural, political and environmental issues as they wrest livelihoods from marginal lands.The cultures, environments and histories of deserts, while fundamentally entangled, are rarely studied as part of a network. To bring different disciplines together, the 1st Oxford Interdisciplinary Deserts Conference in March 2010 brought together a wide range of researchers from backgrounds as varied as physics, history, archaeology anthropology, geology and geography. This volume draws on the diversity of papers presented to give an overview of current research in deserts and drylands. Readers are invited to explore the wide range of desert environments and peoples and the ever-evolving challenges they face.